Cytotoxic activity of carotenoid rich fractions from Haematococcus pluvialis and Dunaliella salina microalgae and the identification of the phytoconstituents using LC‐DAD/ESI‐MS. (29th November 2017) - El‐Baz, Farouk K.; Hussein, Rehab A.; Mahmoud, Khaled; Abdo, Sayeda M.
Abstract : Microalgae represent a rich source that satisfies the growing need for novel ingredients of nutriceuticals, pharmaceuticals, and food supplements. Haematococcus pluvialis and Dunaliella salina microalgae are isolated from the Egyptian hydro‐flora and are reported for their potent antioxidant activities. The cytotoxic activity of different fractions of both microalgae was investigated on 4 cell lines HePG2, MCF7, HCT116, and A549. The carotenoid rich fraction of H. pluvialis showed potent cytotoxic activity against colon cancer cell line and moderate activity against both liver and breast cancer cell lines. On the other hand, the carotenoid rich fraction of D. salina showed mild cytotoxic activity on breast and liver cancer cell lines. The carotenoid rich fraction of H. pluvialis was analysed using LC‐DAD/ESI‐MS and the major carotenoids were identified either free as well as bounded to fatty acids.